Lack of association of metastasis-associated lung adenocarcinoma transcript 1 variants with melanoma skin cancer risk. Issue 6 (December 2019) - Orlandi, Elisa; Zanot, Chiara; Poli, Albino; Nicolis, Morena; Rodolfo, Monica; Turco, Alberto; Sangalli, Antonella; Gomez-Lira, Macarena
Abstract : The long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been implicated in melanoma. Polymorphisms in MALAT1 may play a vital role in the progress of melanoma by its regulative function. However, potential genetic variants in MALAT1 affecting the risk of melanoma onset have not been explored. In this study, two single nucleotide polymorphisms (rs3200401 and rs619586) in MALAT1 were selected for genotyping of 334 melanoma patients and 291 cancer-free controls in an Italian population. The results showed that MALAT1 rs3200401 and rs619586 were not associated with melanoma risk. A further breakdown analysis by sex stratification also indicated a lack of association between these polymorphisms and melanoma. In addition, we tested 450 bp of the proximal 5´ flanking region of the gene for the presence of polymorphisms that could be associated with melanoma risk and found no variants in 96 melanoma patients. In conclusion, our results suggest that there is no contribution of MALAT1 rs3200401 and rs619586 polymorphisms or polymorphisms in the core promoter that could be associated with the risk of melanoma skin cancer in this specific study setting. Further validation will be required in larger studies involving different settings/larger populations in order to reach conclusive results. Abstract : Supplemental Digital Content is available in the text.